TINJAUAN HISTORIS PEMERINTAHAN DINASTI MUGHAL PADA MASA PEMERINTAHAN SULTAN AKBAR TAHUN 1556-1605 M - Putri Dian Pertiwi; Elis Setiawati (Swarnadwipa, 2019)
The presence of the Mughal Empire formed a new civilization in the area which at that time experienced a decline and backwardness. The Islamic Mughal Empire was able to raise the spirit of the Muslims in India. This shows that the Mughal Empire was not the first Islamic empire in India. The purpose of this study is to describe the background of Sultan Akbar's life, to describe the policies implemented by Sultan Akbar, and to describe the influence of the policies implemented by Sultan Akbar in India. This research approach is historical research. This research method uses the Historiography method. This research was conducted at the UM Metro library by reviewing the literature on theMughal Dynasty during the reign of Sultan Akbar. The result of this research is that Sultan Akbar has a brave character and likes to play a role and also he has a tolerant soul, so that when he ruled in the Mughal kingdom he was famous for his tolerance. With the tolerant spirit that Sultan Akbar had, in ruling the Mughal empire he applied the Sulakhul (universal tolerance) policy. It deals with equal rights between Muslims and non-Muslims. Sultan Akbar in addition to implementing Sulakhul politics (universal tolerance), he also carried out various efforts in ruling in the Mughal kingdom including making Khana worship for the king's association with Muslim royal leaders in religious and government matters and making Din-i-Ilahi very controversy.